Achieving Respiratory Health Equality : A United States Perspective - Celedón, Juan Carlos (Respiratory Medicine, 2017)
This book addresses health disparities commonly encountered in pediatric and adult pulmonary, critical care, and sleep medicine, providing a definitive reference on this prominent issue. Expert authors explore questions such as: * What is the evidence that respiratory health disparities exist? * What do we know about the causes of the disparities? * What are the clinical implications? * What can be done to address disparities and thus achieve respiratory health equality? Recognizing the magnitude of this problem, the American Thoracic Society (ATS) Executive Committee created a Health Equality and Diversity Committee, with an initial mandate of defining respiratory health disparities and respiratory health equality in the United States. This book will follow the format of a workshop on respiratory health equality held before the 2015 ATS International Meeting and led by editor Juan Carlos Celedón. Written by the workshop presenters and other distinguished guests, this book will focus closely on major risk factors for disparities in respiratory health, and potential approaches to eliminate such disparities. Achieving Respiratory Health Equality in the United States is a timely resource for researchers, clinicians, and public health practitioners in respiratory medicine.